1985
DOI: 10.1007/bf01458260
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the therapeutic effectiveness of small psychotherapy groups

Abstract: It is generally accepted that a 7-10 member therapy group is the ideal size. The realities of outpatient group psychotherapy, however, are that groups are often considerably smaller than that. Yet, despite these realities, little attention has been paid to how small groups may be effectively led. This paper will examine the dynamics of less-than-ideal-sized groups and suggest how their effectiveness may be maximized. LITERATURE REVIEWMajor literature reviews, such as those by Yalom (1975} andFulkerson, Hawkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…For example, groups may be started for patients with AIDS, eating disorders, or manic depressive illness without waiting for enough prospective members to completely fill a group. Cohen and Rice (1985) point out that overlapping circumstantial and dynamic factors may contribute to groups not filling up. A private practitioner's referral system may be inadequate or the internal dynamics in a clinic administration may be in conflict with the development of groups filling to a robust size.…”
Section: Why Start With a Small Open-ended Unfilled Group?mentioning
confidence: 96%
“…For example, groups may be started for patients with AIDS, eating disorders, or manic depressive illness without waiting for enough prospective members to completely fill a group. Cohen and Rice (1985) point out that overlapping circumstantial and dynamic factors may contribute to groups not filling up. A private practitioner's referral system may be inadequate or the internal dynamics in a clinic administration may be in conflict with the development of groups filling to a robust size.…”
Section: Why Start With a Small Open-ended Unfilled Group?mentioning
confidence: 96%
“…The small membership remained an important factor in the group's life, but similar to the other groups, the men found the experience rewarding and helpful. Although most literature on groups supports the notion of groups larger than four members (Fulkerson et al, 1981;Yalom, 1975), Cohen and Rice (1985) argue that outpatient therapy groups are frequently smaller. Dimock (1988) suggests that six-member groups for adult male survivors provide a safe environment for men to establish trust and allow their vulnerability to show.…”
Section: Group Design and Membership Selectionmentioning
confidence: 98%
“…Although our second group was conducted with three members, we still advocate larger groups considering the difficulties evidenced by small membership. (Cohen & Rice, 1985). A group consisting of four to six members is an ideal size, but, retrospectively, beginning with seven members is suggested due to the high dropout rates these groups frequently produce.…”
Section: Group Design and Membership Selectionmentioning
confidence: 99%
“…Groups with five or more members allow the formation of meaningful relationships [34] and cohesive group functioning [6]. Although some maintain that therapeutic benefit can be derived in groups with < 5 members [35,36], there is evidence that with < 5 members, interaction, group identity, attendance and group image is poor [6,37]. Upper limits to group size may depend on how many people a therapist can practically manage [38] but it has been found that fewer verbal interrelationships occur [33] in groups with > 8 members, and social fission [39] and conflict [40] are more common in larger groups.…”
Section: Group Interventions In Healthcarementioning
confidence: 99%